Testing for food-specific antibodies in saliva and blood of food allergic and healthy dogs. (March 2019) - Udraite Vovk, L.; Watson, A.; Dodds, W.J.; Klinger, C.J.; Classen, J.; Mueller, R.S.
Highlights: Serum and saliva tests showed low sensitivity, specificity, positive and negative predictive values and likelihood ratios. There was no clear difference in the number of positive reactions between allergic and healthy dogs. Serum and saliva tests could not be used to confirm or rule out adverse food reactions. Elimination diets are the reference standard in the diagnosis of adverse food reactions in dogs. Abstract: An elimination diet (ED) followed by re-challenge has been the reference standard to diagnose adverse food reactions (AFR) in dogs, but can be challenging to conduct. This study investigated the accuracy of a saliva-based test for food-specific IgA and IgM and an ELISA serum test for food-specific IgE. Three groups of dogs were tested. Group 1 ( n  = 11) included dogs with previously diagnosed and controlled AFR; group 2 ( n  = 15) comprised dogs with allergic dermatitis at the beginning of their ED; and group 3 ( n  = 16) was composed of clinically healthy research dogs. Saliva samples were collected from all groups and blood samples from group 1 and group 3. The results of clinical re-challenges with individual food components were compared with the test results. Specificity, sensitivity, positive and negative predictive values and likelihood ratios were determined. Forty-one dogs completed the study; one dog was lost to follow up. There was a total of 163 re-challenges. Sensitivity, positive predictive value and likelihood ratio, specificity, negative predictive value and likelihood ratios were unsatisfactory for both tests in most instances, except for IgM testing in group 2, which had moderate specificity. There was no clear difference in the number of positive reactions between the allergic dogs and healthy dogs from a research population. Based on these results, the saliva test for food specific IgA and IgM and the ELISA serum test for food specific IgE were not reliable to diagnose adverse food reactions in dogs. Until more data are available, elimination diets remain the reference standard in the diagnosis of this disease.